Study on Brand Registration in Companies in the Taquari Valley, RS: diagnosis and proposals for improvements - Christ, Vinicius (2023)
The trademark is synonymous with security for the entrepreneur. In this sense, the significant increase in new companies formed and the discrepancy with the number of trademarks deposited, in the same period, raises an alert: are companies unprotected? Thus, this study presents the analysis of how the brands of companies associated with the representative entities of the Chamber of Industry and Commerce of Vale do Taquari are. This is an exploratory research, using bibliography and data analysis. The result showed that 70.6% of the companies analyzed do not have their trademark. Thus, an Institutional Policy was proposed for the CIC VT Entity, in order to encourage trademark registration.